Factors influencing utilization of school health nurse program among secondary students of Lalitpur, Nepal: a mixed-method study - Saraswati Sharma; Anita Mahotra; Tulsi Ram Thapa; Pushpa Thapa; Shital Bhandary; Suraj Bhushal; Sudarshan Paudel (BMC Public Health)
Abstract Background Acknowledging the unique health needs of school children, the Government of Nepal launched the “One School One Nurse” initiative, which was first implemented by the Provincial Government of Bagmati Province in 2018/2019. The program aims to improve health outcomes among school children by deploying a certified nurse in community schools who provides preventive healthcare, health education and first-aid services. Though the program is being scaled up over provinces, it is in its initial stage of development and there are scarce published literature available about the program. This limited availability of comprehensive resources evaluating the program’s usage and supportive and hindering factors demands further investigation on it. Thus, this study assessed the utilization of school nurse services among secondary students and identified the factors associated with service utilization quantitatively. Also, the study explored the underlying factors influencing school nurse service utilization qualitatively. Finally, the study did the triangulation to cross-validate the findings from both quantitative and qualitative studies. Methods A concurrent triangulation mixed-method study was conducted in six public schools randomly selected from each of six local levels of Lalitpur district implementing the ‘’One school one nurse’’ program. Quantitative data were collected from 280 students in grades 9–12 using a self-administered questionnaire. Qualitative data were gathered through in-depth interviews with ten students and key informant interviews with six school staff including school nurses and teachers. Data collection was done from November 2022 to January 2023. Quantitative data were analyzed using weighted multivariable logistic regression to determine predictors of school nurse service utilization. For the qualitative component, a deductive approach based on the socioecological framework was employed to explore factors influencing service utilization. Results The school nurse service utilization rate among secondary students was 28.69% in Lalitpur. The odds of utilizing the service were two times higher among students below 16 years (AOR: 2.08, 95% CI: 1.07–4.02) compared to older students. Additionally, those motivated by teachers, school nurses and parents had four times higher odds of utilization of the service (AOR: 4.16, 95% CI: 1.26–13.64) compared to those without such external encouragement. Conversely, students having learning difficulties had about 68% lower odds of utilizing the school nurse service (AOR: 0.316, CI:0.134–0.744) compared to the student without such difficulties. Triangulation of findings from both studies revealed factors like age, sex, External motivation, student awareness about services and learning difficulty influenced service utilization. Moreover, frequent turnover of school nurses, their absence in school during their training sessions or external programs and insufficient coordination between provincial, local, and school authorities significantly hindered students’ access to services. Ethical approval for the study was obtained by the Institutional Review Committee of Patan Academy of Health Sciences (Ref: PHP2209301678). Conclusions Around one third of secondary students utilized the school nurse services in past one year in Lalitpur district. Enhancing awareness and motivation among students, with a particular focus on older students, male students, and those with learning difficulties, could help increase service utilization rates. Additionally, implementing better staffing strategies and strengthening coordination among stakeholders would enhance program effectiveness, ultimately leading to improved service access. Further research is recommended to examine factors that positively or negatively impact the program at a broader level, incorporating insights from divisional and local level authorities.